A Minibatch Proximal Stochastic Recursive Gradient Algorithm Using a Trust-Region-Like Scheme and Barzilai-Borwein Stepsizes - Yu, T.; Liu, X.W.; Dai, Y.H.; Sun, Jie (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2021)
We consider the problem of minimizing the sum of an average of a large number of smooth convex component functions and a possibly nonsmooth convex function that admits a simple proximal mapping. This class of problems arises frequently in machine learning, known as regularized empirical risk minimization (ERM). In this article, we propose mSRGTR-BB, a minibatch proximal stochastic recursive gradient algorithm, which employs a trust-region-like scheme to select stepsizes that are automatically computed by the Barzilai-Borwein method. We prove that mSRGTR-BB converges linearly in expectation for strongly and nonstrongly convex objective functions. With proper parameters, mSRGTR-BB enjoys a faster convergence rate than the state-of-the-art minibatch proximal variant of the semistochastic gradient method (mS2GD). Numerical experiments on standard data sets show that the performance of mSRGTR-BB is comparable to and sometimes even better than mS2GD with best-tuned stepsizes and is superior to some modern proximal stochastic gradient methods.